Computing Technologies: A Cornerstone for Educational and Employment Equity - Hollingsworth, Maurice (Canadian Journal of Higher Education, 1992)
The rate of employment for people with disabilities is very low relative to employment levels of non-disabled people. One factor that appears to contribute to greater employment is the level of education achieved by the individual. The impact of higher levels of education on employment is reflected in the general population, but is particularly apparent in the statistics of people with disabilities. Unfortunately, disproportionately few people with disabilities take advantage of postsecondary education. Technology is important for people with disabilities as a vehicle to education and eventually to employment. Computing technologies have been demonstrated as a powerful assistive tool to aid people with disabilities in an academic environment, especially as we are rapidly moving into the information age. These factors lead to the recommendation that we need to (a) provide "equity tools" for disabled students in postsecondary settings to enable access to computing technologies, (b) provide accompanying instruction and academic support, (c) educate students in the human services fields in the roles and processes of computing technologies, and (d) research and disseminate information on the equity tools and applications of these tools.